2020
DOI: 10.1590/1807-3107bor-2020.vol34.0093
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative molecular analysis of bacteria in root canals of primary teeth with pulp necrosis

Abstract: Information about bacterial diversity, such as the number of each species in the root canals of primary teeth, contributes to improving our effective management of infections of endodontic origin in primary teeth. This study made a qualitative and quantitative assessment of the bacteria in the root canals of primary teeth with necrotic pulp, using the fluorescence in situ hybridization (FISH) technique. Thirty-one primary teeth with pulp necrosis from 31 children were evaluated using the FISH technique, to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…However, sodium hypochlorite (NaOCl) is considered the widely used endodontic irrigant solution but it has numerous disadvantages such as bad taste, toxicity, and risk of tissue destruction and denatures, as well as the inability to eliminate all the microorganisms present in infectious canals. Chlorhexidine (CHX) gluconate can be applied clinically as an antimicrobial agent alone or in combination with NaOCl during all phases of the root canal preparation (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sodium hypochlorite (NaOCl) is considered the widely used endodontic irrigant solution but it has numerous disadvantages such as bad taste, toxicity, and risk of tissue destruction and denatures, as well as the inability to eliminate all the microorganisms present in infectious canals. Chlorhexidine (CHX) gluconate can be applied clinically as an antimicrobial agent alone or in combination with NaOCl during all phases of the root canal preparation (4) .…”
Section: Introductionmentioning
confidence: 99%
“…However, the endodontic infections have a polymicrobial nature but it was found that Enterococcus faecalis (E. faecalis) is one important microorganism to be controlled as it observed in 22% and 32% of necrotic deciduous teeth and it is more prevalent in secondary infection than in primary endodontic infections. Additionally, it has been considered as the most antibioticresistant and the most common species recovered from teeth with failed endodontic treatment (4) . However, no irrigant solution appears to be ideal as a disinfectant solution against E. faecalis.…”
Section: Introductionmentioning
confidence: 99%
“…(9,10,15) Muchos investigadores han demostrado que existe una gran diversidad bacteriana en piezas dentarias con necrosis; en dientes permanentes se han aislado microorganismos como: Streptococcus salivarius, Streptococcus mutans, Staphylococcus aureus, Neisseria catarrhalis, Lactobacillus casei, Pseudomonas aeruginosa, Candida albicans, Enterococcus faecalis entre otros (9,10,15) . En dientes temporales se han aislado microorganismo como: Streptococcus salivarius, Streptococcus muntans, Streptococcus sobrinus, Prevotella intermedia, Provotella nigrescocens, Porphyromona gingivalis, Treponema denticola, entre otros (16,17,18) . Pero las bacterias anaerobias facultativas son las especies dominantes involucradas en este proceso, entre ellas, el Enterococcus faecalis que también es considerado como el microorganismo más resistente y responsable de los fracasos de los tratamientos pulpares en dientes temporales y permanentes.…”
Section: Planteamiento Del Problemaunclassified